Coupling land-use change and hydrologic models for quantification of catchment ecosystem services. (November 2018) - Yalew, S.G.; Pilz, T.; Schweitzer, C.; Liersch, S.; van der Kwast, J.; van Griensven, A.; Mul, M.L.; Dickens, C.; van der Zaag, P.
Abstract: Representation of land-use and hydrologic interactions in respective models has traditionally been problematic. The use of static land-use in most hydrologic models or that of the use of simple hydrologic proxies in land-use change models call for more integrated approaches. The objective of this study is to assess whether dynamic feedback between land-use change and hydrology can (1) improve model performances, and/or (2) produce a more realistic quantification of ecosystem services. To test this, we coupled a land-use change model and a hydrologic mode. First, the land-use change and the hydrologic models were separately developed and calibrated. Then, the two models were dynamically coupled to exchange data at yearly time-steps. The approach is applied to a catchment in South Africa. Performance of coupled models when compared to the uncoupled models were marginal, but the coupled models excelled at the quantification of catchment ecosystem services more robustly. Highlights: Calibrated and dynamically coupled a land-use change model and a hydrologic model. Analyzed effects of the dynamic feedback between the two on quantification of ecosystem services. Coupled models performed only slightly better at capturing observation on both models. Coupled models produced a more robust quantification of catchment ecosystem services.